Functional validation of genetic variants identified by next generation sequencing in malformations of cortical development - De Vita, Dalila (Premio Tesi di Dottorato, 2021)
Malformations of cortical development (MCDs) result from a disruption in the process of the human brain cortex formation: currently, there are no pharmacological treatments for diffuse MCDs. Next-generation sequencing has accelerated the identification of MCDs causing genes: in some cases, functional studies are needed to clarify the role of genetic variants. The aim of this PhD project has been to apply a multidisciplinary approach to identify causative mutations in patients with MCDs, validate the pathogenic role of the identified mutations, and assess the effectiveness of novel in vitro treatment for mTOR pathway related MCDs.